THE FERGANA TYPE OF PERMANENT HOUSING IN THE SOUTH OF KYRGYZSTAN IN THE FIRST HALF OF THE 20TH CENTURY. (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines permanent dwellings of the Fergana type, common in the south of Kyrgyzstan in the first half of the 20th century. Particular attention is paid to the architectural and planning features of this type of dwelling, its adaptation to the natural and climatic conditions of the region and transformation under the influence of socio-economic changes. The study is based on historical and ethnographic materials, archival documents and field research. The influence of the traditions of sedentary agriculture and intercultural interaction on the formation of the unique architectural appearance of the houses is analyzed. Fergana-type dwellings are not only a functional form of life, but also an important element of the cultural heritage of the region, reflecting the ethnic identity and historical development of the southern regions of Kyrgyzstan. The article also examines the design and interior of permanent houses of the Fergana type in the south of Kyrgyzstan.
Keywords: Fergana Valley, Kyrgyz, dwelling, house, “paksa”, “synch”, “kysh”, “peshaivan”.